What is needed to improve quality of implant removal services in Nigeria? results of a landscape assessment - Adetiloye, Oniyire; Danladi, Abubakar; Haws, Rachel; Anoke, Charity; Odio, Bartholomew; Ugwa, Emmanuel; Nganje, Agnes; Enne, Joseph; Afolabi, Kayode; Adebola, Owodunni; Eze, Justus; Christofield, Megan (Frontiers in Global Women's Health, 2023)
Introduction: Stunning recent increases in subdermal contraceptive implant use, especially in sub-Saharan Africa, necessitate availability of quality implant removal services. In Nigeria, service delivery capacity and coverage for removal are lacking, despite strong government commitment and rapid uptake; there is a dearth of knowledge about barriers to quality implant removals in Nigeria. Methods: To determine access to and quality of contraceptive implant removal services, a landscape assessment was conducted in two states in Nigeria, focusing on four conditions for quality delineated in the Global Implant Removals Task Force framework. This mixed-methods approach integrated results from a desk review, a survey of health facilities and family planning managers, review of implant service statistics, and key informant interviews with providers and diverse stakeholders. Results: Seventy percent of providers (N=21 of 30) had experienced problems performing implant removal, usually due to deeply inserted implants and equipment shortages. Providers had low confidence in performing removal and poor knowledge of implant removal steps. No facilities assessed had comprehensive equipment required for implant removal. Few facilities maintained systems or referral pathways to support difficult removals; difficult removals are absent from training manuals, and no formal trainings have been conducted. While most facilities collect data on removals, family planning dashboards do not capture it; few facilities use data for quality improvement. Conclusion: This study identified numerous challenges to quality implant removal, including poorly trained providers, inadequate supplies, underutilization of data on removals, and inability to manage difficult removals. As demand for implant removals skyrockets, providers need improved training in implant removal, appropriate job aids, supportive supervision, and effective procurement systems to ensure availability of supplies and equipment for removal. Tracking removals and reasons for removal in information systems and the Family Planning dashboard could sensitize providers to need for implant removals and improve data for decision-making in facilities and health systems.